Implementasi Model Pembelajaran Predict Observe Explain (POE) Untuk Meningkatkan Hasil Belajar Siswa Kelas V SD Negeri 0117 Sibuhuan - Anisa Wahyuni Hasibuan; Nurhayati Siregar; Nunrhalimah Harahap (Simpati, 2023)
The aim of this research is to determine the improvement in student learning outcomes in the science subject light and its properties in class V of SD Negeri 0117 Sibuhuan through the application of the predict observe explain (POE) learning model. The methodology used is Classroom Action Research (PTK) which consists of 2 cycles, each cycle consisting of planning, implementation, observation and reflection. Based on the results of the research carried out by the author, it can be concluded that the increase in student learning outcomes in science subjects is light and nature. -class V of SD Negeri 0117 Sibuhuan through the application of the predict observe explain learning model (pre-cycle POE is still low, namely students who scored above the KKM 70, there were 7 students with a percentage of 25.00% and 21 students scored below the KKM with a percentage of 75, 00%. In cycle I it has started to increase, namely there are 17 students who got a score above the KKM 70 with a percentage of 60.71% and 11 students got a score below the KKM with a percentage of 39.29%. In the second cycle it has increased, namely there are 26 students who got a score above the KKM 70 with a percentage of 92.86% and 2 students got a score below the KKM with a percentage of 7.14%. So it can be concluded that by implementing the Predict Observe Explain (POE) learning model in the science subject light and its properties in Class V of SD Negeri 0117 Sibuhuan, student learning outcomes can be improved